Strategi Meningkatkan Loyalitas Pelanggan Pada PT Golden Batam Raya - Hendri Herman (JURNAL AKUNTANSI BARELANG, 2020)
The purpose of this study is to look at customer loyalty in terms of price. The study was conducted at PT Golden Batam Raya with total sample of 92 respondents. The results of this study that price has a significant effect on customer loyalty. The percentage of price effect on customer loyalty is 45,1%. This value is large enough so that it is important fot the object of research to pay attention to the policies taken in setting the selling price of the product